Hirarki Kebutuhan Tokoh Utama dalam Novel Pulang dan Laut Bercerita Karya Leila S. Chudori (Kajian Psikologi Humanistik Abraham Maslow) - Gaby Rostanawa (Universitas Negeri Surabaya, 2019)
This research has the purpose to analyze and describe the hierarchy of needs experienced by the main character in the novel Pulang and Laut Bercerita by Leila S. Chudori, so it can be seen form of fulfillment needs. This study used descriptive qualitative method. The data in this research are the dialogues, sentences, phrases and words of the main character the novel Pulang and Laut Bercerita by Leila S. Chudori. Data collection techniques used are data sources, reading and record techniques, data reduction, data categories, then corpus data. From the results of analysis and discussion, there is the conclusion that in the novel Pulang and Laut Bercerita by Leila S. Chudori, found various forms of fulfillment needs done by the main character. Keywords: Novel, Hierarchy of Needs, Humanistic Abraham Maslow